To Teach Higher Education Students General Didactic Principles and Methods of using New Pedagogical Technologies in Music Culture Lessons - Mavludaxon Rahimova Nabijonovna (Research Parks Publishing LLC, 2021)
The famous historian Sharafiddin Ali Yazdi in his book